O tempo e o impacto da experiência estética na era da Pre(s)sa: psicanálise e teatro performático - Fazzio, Fernanda Esteves (2019)
The following research establishes dialogues between psychoanalysis and art by reflecting on the very experiences that involve time — as it is here called the “era of haste” — and the effects that the artistic impact may produce within subjects. The performative theatre of the play “...In between intervals...” (...Entre Esperas...) is considered as a possible cultural space, which amplifies symbolical webs, constructs narratives and connects signifiers that may be craved on the subjects’ psychic system by means of an opening to the novelty caused by an intense aesthetic experience. The complex “era of haste”, characterized by the accelerated rhythm contained in the profusion of tasks and demands, suffocates the individuals chained to an ever-insufficient time. As a result, their inner world may be symbolically impoverished and confined to limited experiences, since time to elaborate ideas and the psychic labour itself are compressed under social ideals. This Master’s dissertation was developed according to Psychoanalysis’ research methodology, namely by articulating the epistemology present in both Psychoanalysis and Arts, hence compatible with the exercise of the so-called implied psychoanalysis (Psicanálise implicada) according to Renato Mezan’s e João Frayze-Pereira’s studies. The main psychoanalytical authors summoned in this research are Sigmund Freud, Jacques Lacan, Sándor Ferenczi and Jean-Bertrand Pontalis all of which contribute to articulate time, memory and trauma. Philosophers and sociologists, such as Walter Benjamin, Zygmunt Bauman, Gilles Lipovetsky, Georg Simmel and Byung-Chul Han contributed to contextualize the concept of time in the “era of haste” with special regard to the contradiction of excesses and its instrumental character, which produces effects in regards to time management. Trauma and the Unheimliche were articulated in view of the works from Oscar Cesarotto and Alessandra Martins Parente in order to address the effects and impacts of the aesthetic experience. The contributions of psychoanalyst contemporaneous Maria Rita Kehl, Julieta Jerusalinsky, Joel Birman, Ana Costa and Paula Peron played a fundamental role in establishing connections amongst subjectivity, trauma and uneasiness in the “era of haste”, hence depicting the foundations to analyse the play “In between intervals” (Entre Esperas)